Microchannel Flow Dynamics and Heat Transfer of Near-Critical Fluid - Chen, Lin (Springer Theses, Recognizing Outstanding Ph.D. Research, 2017)
This book discusses basic thermodynamic behaviors and 'abnormal' properties from a thermo-physical perspective, and explores basic heat transfer and flow properties, the latest findings on their physical aspects and indications, chemical engineering properties, microscale phenomena, as well as transient behaviors in fast and critical environments. It also presents the most and challenging problems and the outlook for applications and innovations of supercritical fluids. .